2001
DOI: 10.2460/javma.2001.218.1973
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an inactivated respiratory syncytial virus vaccine in calves

Abstract: Results suggest that the inactivated BRSV vaccine provided clinical protection from experimental infection with virulent virus and decreased the severity of pulmonary lesions. Efficacy was similar to that reported for modified-live BRSV vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 25 publications
5
50
1
2
Order By: Relevance
“…Good levels of Th1 and Th2 responses are elicited by the use Quil A as an adjuvant (ELLIS et al, 2005). The results obtained here and those previously reported in the literature for the immunization using BRSV-saponin-adjuvanted vaccines should be taken with caution, since the results were obtained in a mice model.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…Good levels of Th1 and Th2 responses are elicited by the use Quil A as an adjuvant (ELLIS et al, 2005). The results obtained here and those previously reported in the literature for the immunization using BRSV-saponin-adjuvanted vaccines should be taken with caution, since the results were obtained in a mice model.…”
Section: Discussionsupporting
confidence: 41%
“…Vaccines have Ciência Rural, v.40, n.11, nov, 2010. been used at least for the last 30 years to control BRSV infections in cattle (KERKHOFS et al, 2004;LETELLIER et al, 2008) and nowadays there are a number of commercially available BRSV vaccines (ELLIS et al, 1995;HÄGGLUND et al, 2004); whose use is controversial since its efficacy and potential enhancement of disease in vaccinated animals are not well documented under field conditions (SCHREIBER et al, 2000;LARSEN et al, 2001). Experimental assays using Modified-life virus (MLV) or inactivated vaccines (ELLIS et al, 1995(ELLIS et al, , 2005 showed different degrees of protection against pulmonary pathology induced by the challenge as well as production of neutralizing and non-neutralizing antibodies to BRSV, on the dependence of the type of vaccine and adjuvant used (ELLIS et al, 2001(ELLIS et al, , 2005. On the other hand, animals vaccinated using BRSV inactivated virus, produced high levels of total anti-BRSV IgG antibodies and lower titres of BRSV-neutralizing antibodies (ELLIS et al, 1995(ELLIS et al, , 2005PATEL & DIDLICK, 2004;MAWHINNEY & BURROWS, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total lung area involved in lesions was calculated as previously described [9][10][11]. Briefly, tracings were made on acetate from the projected images of the dorsal surface area of the lungs, outlining obviously pneumonic/edematous areas, as well as the total lung area.…”
Section: Macroscopic and Microscopic Pathologymentioning
confidence: 99%
“…Although several parenteral vaccines are licensed and have been shown to be effective for use against hRSV in cattle [8][9][10][11], there is currently no vaccine available for the prevention of hRSV in human infants [12][13][14][15]. Recent interest in the use of intranasal vaccines for respiratory diseases in children has emerged, and an intranasal vaccine for influenza has recently been shown to be safe and effective in young children [16].…”
Section: Introductionmentioning
confidence: 99%